Crystal structure and infrared analysis of a new trinuclear platinum(II) complex with L-cysteine - Corbi, Pedro P.; Castellano, Eduardo E.; Cagnin, Flavia; Massabni, Antonio Carlos [UNESP] (Springer, 2007)
A new trinuclear platinum(II) complex with cysteine of composition [Pt(C3H6NO2S)Cl](3)center dot(C2H6SO)(3) was obtained and structurally characterized by X-ray diffraction and infrared analysis. The compound crystallizes in the trigonal system, space group R3, and is described in a hexagonal cell with a=17.739(1), c=9.531(1) and Z=3. Cysteine is coordinated to Pt(II) through the nitrogen and sulphur atoms. Each cysteine sulphur bridges between two metal atoms. A square planar coordination sphere of platinum is completed by a chlorine atom. The complex is soluble in dimethyl sulfoxide.
Keywords: platinum; cysteine; crystallography; X-ray; infrared analysis